THE SOUND OF EVIL: A PERSPECTIVE OF COMPARATIVE LITERATURE - Purnomosasi, Lusia Kristiasih Dwi (Paramasastra: Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2014)
The representation of evil in The Scarlet Letter, Madam Bovary, Anna Karenina, and Lady Chatterley’s  Lover  is  a  choice  to  be  compared  by  the  theory  of  comparative literature of Claudio Guillen.It  is  called  thematology.  It  is  based on  the assumption that a theme will be different as  it is accepted by different cultures. Internationality is applied among others. The evil functions as a representation of a sinner in The Scarlet Letter in line with external marital affairs by the main character. It is due to the belief of  witch  that  leads  to  the  special  woman.  The  witch  as  the  representation  of  evil changes  to  the  beggar  in  Madam  Bovary  and  a  railway  station  officer  in  Anna Karenina. Both  reflect  the different  social  stratification as  the effect of materialism. Lady Chatterley’s Lover  has  transformed  to an  invisible  representation of evil.  It  is the mentality of capitalism. The  transformation of  those evil  in  the novels  is created from the stereotype towards the cursed by society. It deals with the belief and status.